Effect of Rice Beer and Phyto-Ingredients on Proximate Composition, Texture, Colour, and Sensory Evaluation of Vacuum-packaged Marinated Duck Meat - Pompi Rani Boro; Saurabh Kumar Laskar; Ankur Das; Naba Jyoti Deka (Archives of Current Research International, 2025)
This research investigates the impact of rice beer and phyto-ingredients on vacuum-packaged marinated duck meat quality. Ducks aged 9 to 12 months were sourced, slaughtered, and dressed, followed by marination in four formulations: a control (meat + spice paste), T1 (meat + rice beer + spice paste), T2 (meat + phyto-ingredients + spice paste), and T3 (meat + rice beer + phyto-ingredients + spice paste). After marination, the samples were vacuum-packaged and refrigerated for 24 hours, with quality assessments conducted at 5-day intervals. Results showed that T3 had significantly higher moisture content than the control, while the control had higher levels of crude protein, ether extract, and total ash. Colour analysis indicated no significant differences in lightness, but a decrease in redness and yellowness was noted across samples. Texture analysis revealed T3 had reduced hardness, with significant differences in springiness and chewiness compared to the control. Sensory evaluation showed no significant differences in appearance, colour, flavour, or tenderness but notable differences in juiciness and overall acceptability.